2+(9+1)=12
1) 9+1=10
2)2+10=12
5+(10-1)-(1+3)=10
1) 10-1=9
2)1+3=4
3)5+9=14
4)14-4=10
7+9-(8-7)=15
1) 8-7=1
2)7+9=16
3)16-1=15
А)8х-7х+10=12
х=12-10
х=2
б)13у+15у-24=60
28у=60+24
28у=84
у=84:28
у=3
в)3z-2z+15=32
z=32-15
z=17
г)6t+5t-33=0
11t=33
t=33:11
t=3
д)(х+59):42=86
х+59=86*42
х+59=3612
х=3612-59
х=3553
е)528:к-24=64
528:к=64+24
528:к=88
к=528:88
к=6
<span>6(х-3)=4х
</span><span>6х-18=4х
</span><span>6х-4х=18
</span><span>2х=18
</span><span>х=9</span><span>
1)9*4=36 (стр)
Ответ: 36 стр.
</span>